Impact of ABCB1 and CYP2D6 polymorphisms on tamoxifen treatment outcomes and adverse events in breast cancer patients - Argalacsova, Sona; Slanar, Ondrej; Bakhouche, Hana; Pertuzelka, Lubos (Journal of B.U.ON., 2017)
PURPOSE: This study was designed to evaluate the effect of CYP2D6 and ABCB1 polymorphisms and co-medication on the outcomes and adverse events (AEs) of tamoxifen therapy. METHODS: In total, 258 women (187 postmenopausal and 71 premenopausal) with hormone positive breast carcinoma were retrospectively evaluated. CYP2D6 polymorphisms were evaluated with AmpliChip (Roche), and polymorphisms of ATP-binding cassettes B1 (P-glycoprotein) (ABCB1) rs2032582 and rs1045642 with restriction fragment length polymorphisms polymerase chain reaction (RFLP-PCR). RESULTS: CYP2D6 polymorphisms or co-medication affecting CYP2D6 activity demonstrated no statistically significant effect on the efficacy of tamoxifen therapy or AE incidence. There was only a trend towards shortening the time to event (TTE) in CYP2D6-poor metabolisers. ABCB1 polymorphism rs2032582 was not associated with clinical outcomes, while a trend towards an increase in TTE, in variant allele carriers, was noted. The ABCB1 polymorphism rs1045642 demonstrated statistical significance, albeit only in premenopausal patients, i.e. the effect of two variant alleles on the TTE extension was demonstrated only in the premenopausal group (p=0.0012, HR 0.69; 95% CI 0.21-2.31), and statistical significance (p=0.0106) only for gynaecological/vasomotor AEs (p=0.0221, HR=1.0588), with no evidence of any influence on the incidence and onset of venous complications (i.e. deep venous thrombosis or pulmonary embolism). CONCLUSIONS: Although no conclusive statistical association between the examined polymorphisms and the outcome or incidence of AEs in tamoxifen therapy was found, the impact of ABCB1 polymorphisms warrants further research. The importance of finding predictive pharmacogenomic biomarkers is a major challenge for individualization and pharmaco-economic rationalization of therapy. The latest international guidelines support this notion.
Keywords: Humans; Estrogen Antagonists; lidé středního věku; polymorfismus genetický; Female; dospělí; Tamoxifen; výsledek terapie; lidé; ATP Binding Cassette Transporter, Subfamily B; Polymorphism, Genetic; tamoxifen; Adult; Breast Neoplasms; ženské pohlaví; cytochrom P-450 CYP2D6; Middle Aged; Retrospective Studies; P-glykoproteiny; Cytochrome P-450 CYP2D6; Treatment Outcome; nádory prsu; retrospektivní studie; antagonisté estrogenu